Off-farm employment participation among paddy farmers in the Muda Agricultural Development Authority and Kemasin Semerak granary areas of Malaysia - Man, Norsida; Ismaila, Sadiya Sami (Macroeconomic Policy and Development Division of the United Nations Economic and Social Commission for Asia and the Pacific, 2009)
Poverty is one of the most serious challenges confronting paddy farmers worldwide, including those in Malaysia. Off-farm employment is an alternative strategy and has the potential to improve the income and well-being of the paddy farmers. This study assesses the off-farm employment decision among 500 paddy farmers in the Muda Agricultural Development Authority and Kemasin Semerak granary areas. Specifically, the study determines the relationship between the determinants of off-farm employment and the off-farm participation decision using descriptive analysis and logit regression methods. The results reveal that the farmers’ age, gender and number of dependants, as well as other income and the type of farm were the variables that influenced their likelihood to engage in off-farm employment. Evidently, the variables of farm size and level of education were insignificant in affecting off-farm participation.